Cytopathologic findings and differential diagnostic considerations of primary clear cell carcinoma of the lung. Issue 6 (11th October 2011) - Hayashi, Toshitetsu; Haba, Reiji; Kushida, Yoshio; Kadota, Kyuichi; Katsuki, Naomi; Miyai, Yumi; Bando, Kenji; Shibuya, Shinsuke; Matsunaga, Toru; Yokomise, Hiroyasu
Abstract Primary clear cell carcinoma (CLCC) of the lung is an extremely rare disease and is a subtype of large cell carcinoma, according to the World Health Organization (WHO) classification. A case is presented here in which intraoperative squash smears in a 53‐year‐old man revealed sheet and small clusters or tumor cells with prominent nucleoli and fine granular chromatin. Abundant translucent cytoplasm with occasional cytoplasmic vacuoles and intracytoplasmic eosinophilic inclusions was also identified. A cytopathologic diagnosis of a CLCC was suggested. Further evaluation and immunohistochemical studies were conducted on formalin‐fixed, paraffin‐embedded material. Nests of slightly acidophilic clear tumor cells with a prominent cellular membrane and an alveolar growth pattern were identified on H&E sections. Immunohistochemically, the tumor cells showed diffuse and strong membranous staining for CK(AE1/AE3), CK7, and CA19‐9 but were negative for Napsin A, CK20, CDX2, TTF‐1, alpha‐fetoprotein, chromogranin A, synaptophysin, CD10, and CD56. The diagnosis of primary CLCC of the lung was confirmed based on cytopathologic, histopathologic, immunohistochemical results, and a detailed systemic examination to exclude a possible extrapulmonary origin. We report here the cytopathological features of CLCC of the lung with an emphasis on differential diagnostic considerations. Diagn. Cytopathol. 2013. © 2011 Wiley Periodicals, Inc.